383 RELATION OF OBESITY TO DECREASED SPERM COUNT. Issue 1 (1st January 2007) - Hammoud, A.; Parks, A.; Gibson, M.; Carrell, D. T.; Peterson, C. M.; Meikle, A. W.
Abstract : Objectives: Obesity is increasingly recognized as a cause of reduced male fertility through multiple mechanisms. The purpose of this study is to investigate the relationship between body mass index and sperm count. Materials and Methods: We reviewed records of male partners of couples seeking treatment at the fertility center over the last 3 years. Data collected included patients' demographics, past medical and surgical history, and risk factors for male infertility. Body mass index (BMI) (kg/m 2 ) was calculated. Semen analysis was performed within the month, which included semen volume (mL), sperm concentration (sperm count/mL), progressive motility (% progressive motile sperm), and morphology (% normality of different morphologic features of sperm). Chi-square (with Fisher correction if needed) was used to compare frequencies. Pearson correlation was used when appropriate. Results: 257 patients were included in this analysis and had a mean age 32.5 ± 0.37 years. The BMI distribution is shown in the table . The mean sperm count was 110.8 ± 2.9 million sperms/mL. A low sperm was defined using the World Health Organization criteria for low sperm count (< 20 million sperm/mL), which was 10.7% of patients, and sperm motility was 46 ± 0.6%. The frequency of low sperm count according to the BMI category is given in Table 1 . Low sperm count was more frequent in obese and overweight males than in normal weight men. There was also a negative correlation between BMI and sperm motility (Pearson r = −.13, p = .04), but no age effect. Conclusion: Our findings suggest that obese and overweight men are more likely to have low sperm count and decreased sperm motility, which might reduce fertility.